Pelatihan Perencanaan Keuangan, Peluang Bisnis Ibu Rumah Tangga dan Pelaporan Keuangan Sederhana UMKM - Yudhi Prasetiyo; Sila Ninin Wisnantiasri; Nindya Farah Dwi Puspitasari; Shufia Zuhroh; Nadhira Hardiana; Irma Irma (I-Com: Indonesian Community Journal, 2024)
Women's role in improving the family economy and MSMEs in the village economy is one of the keys to improving welfare for both the family and society as a whole. Family financial planning, creating new business opportunities and creating good financial documentation for MSMEs is one of the keys to how housewives and MSMEs can make a good contribution to organizing and developing their competence to build the economic level in the village and area where they live. The method used is by means of discussion, training, providing modules and mentoring. The results of this activity provide positive implications for how enthusiastic housewives and MSME actors in Situ Udik Village can improve their competence and skills to build a better economy. The result of 1) Housewives can make good and healthy financial plans for their family life, (2) Provide potential benefits for housewives to earn additional income to improve their family's economy, (3) Increase knowledge for MSMEs in the village area to be able to make simple financial reports according to the correct provisions so that the financial health of the business is maintained. This National Community Service was carried out in Situ Udik Village, Cibungbulang District, Bogor Regency, West Java. Limited knowledge and competence of MSMEs and housewives in the field of accounting, and lack of motivation for housewives to work to create new business opportunities.